Pleomorphic adenoma of palpebral lobe of lacrimal gland masquerading as skin adnexal tumor of eyelid - Dr. Sujata S Giriyan; Dr. Akanksha Agrawal; Dr. Rajesh H Chandan (Tropical Journal of Pathology and Microbiology, 2017)
Occurrence of Lacrimal gland tumorsis rare. Benign epithelial tumors are more common of which pleomorphic adenoma is commonest. They usually occur in the orbital lobe of lacrimal gland however, they mayrarely occur in palpebral lobe. FNAC helps to rule out other pathologies and narrows the differential diagnosis. We describe a case of young female who presented with a nodular right upper eyelid swelling, clinically diagnosed as a skin-adnexal tumor. On FNAC, diagnosis of Chondroidsyringoma of skin adnexawas given. Histopathologically however it was confirmed to be Pleomorphic adenoma of lacrimal gland. Although rare, possibility of both chondroidsyringoma and pleomorphic adenoma of palpebral lobe of lacrimal gland should be considered in case of a mobile, nodular swelling in the upper eyelid. FNAC aids in diagnosis, however, histopathological examination remains the diagnostic gold standard.